2016
DOI: 10.1177/0269215515610039
|View full text |Cite
|
Sign up to set email alerts
|

The effects of resistance exercise in patients with knee osteoarthritis: a systematic review and meta-analysis

Abstract: Resistance exercise is beneficial in terms of reducing pain, alleviating stiffness, and improving physical function in patients with knee osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 40 publications
(121 reference statements)
4
75
0
3
Order By: Relevance
“…Other studies 21 corroborate these findings, showing that weight exercises are effective in improving the pain of these patients.…”
Section: Discussionsupporting
confidence: 59%
“…Other studies 21 corroborate these findings, showing that weight exercises are effective in improving the pain of these patients.…”
Section: Discussionsupporting
confidence: 59%
“…In this sense, countless studies and reviews involving therapeutic exercise and resistance exercise have demonstrated success in the reduction of pain in these patients, 11,12,14,[26][27][28][29] which can cause a natural increase in the level of physical activity, helping control weight and increasing physical capacity.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Thus, therapeutic exercise is recommended in numerous guidelines as the non-pharmacological intervention for the treatment of knee OA. 13,14 However, it is worth emphasizing that there is still no consensus as to the parameters for the intensity and duration of each type of exercise.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance training is an exercise intervention that has been utilised to decrease symptoms, impairment, and improve function in individuals with OA at the knee and hip [9, 10]. Several studies have demonstrated its effectiveness and this treatment modality is included in the American College of Rheumatology 2012 treatment guidelines for knee and hip OA, but not for hand OA [11].…”
Section: Introductionmentioning
confidence: 99%